Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1073/pnas.93.18.9899
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of gamma-aminobutyric acid type A receptors is determined by receptor beta subunits.

Abstract: y-aminobutyric acid type A (GABAA) receptors are the major sites of fast synaptic inhibition in the brain. They are constructed from four subunit classes with multiple members: a(1-6), ,3(1-4), y(1-4), and 6(1). The contribution of subunit diversity in determining receptor subcellular targeting was examined in polarized Madin-Darby canine kidney (MDCK) cells. Significant detection of cell surface homomeric receptor expression by a combination of both immunological and electrophysiological methodologies was onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
1
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 23 publications
9
98
1
2
Order By: Relevance
“…5, E and F). These results are in agreement with previous reports demonstrating that ␤ 3 subunits are able to form homo-oligomeric receptors that are expressed on the cell surface (21,30). The observation that the truncated and the full-length subunit could be detected in the permeabilized cells in the same subcellular compartments (Fig.…”
Section: Figsupporting
confidence: 83%
See 1 more Smart Citation
“…5, E and F). These results are in agreement with previous reports demonstrating that ␤ 3 subunits are able to form homo-oligomeric receptors that are expressed on the cell surface (21,30). The observation that the truncated and the full-length subunit could be detected in the permeabilized cells in the same subcellular compartments (Fig.…”
Section: Figsupporting
confidence: 83%
“…These subunits are able to form pentameric receptors (12) and are expressed on the cell surface (4,21,30). C-terminally truncated ␣ 1 or ␤ 3 subunits, containing only the extracellular Nterminal domain also could assemble with each other or with full-length ␤ 3 or ␣ 1 subunits, respectively, but the assembly products remained in intracellular compartments and could not be detected on the cell surface.…”
Section: (1-9) Antibodies (A C E G I K M and O) And Bd17 Antibmentioning
confidence: 99%
“…Although homo-oligomeric receptors composed of ␤ 3 subunits could also have been formed under the conditions used, they would not have contributed to the GABA evoked current because these receptors apparently are not gated by GABA (Connolly et al, 1996b). Using various GABA concentrations, it was demonstrated that GABA exhibited an EC 50 of 10.5 Ϯ 2.1 M (mean Ϯ SEM; n ϭ 8 cells from different plates; total of four transfections) (Fig.…”
Section: Amino Acid Sequence ␣ 1 (80-100) Mediates Binding To ␥ 2 Submentioning
confidence: 99%
“…The targeting of GABA A (Connolly et al, 1996) or glutamate receptors depends on the identity of the subunits forming the receptors. In addition, the composition in subunits also controls the local movements of glutamate receptors (Shi et al, 2001).…”
Section: Intracellular Targeting and Receptor Clusteringmentioning
confidence: 99%